1990
DOI: 10.1111/j.1399-6576.1990.tb03032.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thoracic epidural anaesthesia on central haemodynamics compared to cardiac beta adrenoceptor blockade in conscious rats with acute myocardial infarction

Abstract: The study aimed to compare the effects of thoracic epidural anaesthesia (TEA) with those of the beta-adrenoceptor blocker, metoprolol, on central haemodynamics in conscious rats with acute myocardial infarction. During methohexital anaesthesia, appropriate vascular catheters were inserted, a thoracic epidural catheter was implanted and the left coronary artery was ligated. A recovery period of 1-2 h elapsed after termination of surgery and anaesthesia. Experiments were performed on four separate groups of anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Experimental and clinical data reported improvement in left ventricular function in coronary artery disease, unstable angina pectoris, and myocardial infarction with TEB [4][5][6][7][8][9]. Hypothetically, the blockade of hyper-activated sympathetic nerves by TEB could be helpful in patients with IDCM and heart failure (HF).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Experimental and clinical data reported improvement in left ventricular function in coronary artery disease, unstable angina pectoris, and myocardial infarction with TEB [4][5][6][7][8][9]. Hypothetically, the blockade of hyper-activated sympathetic nerves by TEB could be helpful in patients with IDCM and heart failure (HF).…”
mentioning
confidence: 97%
“…The introduction of dedicated guidewires and the development of new techniques have improved the success rate in the crossing of CTO lesion while the widespread use of drug-eluting stent (DES) has reduced the occurrence of restenosis and the need for target lesion revascularization [3]. Of note, two recent meta-analysis showed that first-generation DES use was associated with a lower rate of major adverse cardiovascular events (MACEs), as compared to bare-metal stent (BMS), both at mid-and long-term follow-up [4,5]. However, some concerns about long-term complications of DES implantation [late restenosis and stent thrombosis (ST)] are emerging [6,7].…”
mentioning
confidence: 99%
“…A comparison between thoracic epidural anaesthesia and b-AA on haemodynamic parameters in conscious rats with acute myocardial infarction revealed the following intriguing ®ndings. 10 While thoracic epidural anaesthesia decreased left ventricular end-diastolic pressure and systemic vascular resistance remained unaffected, metoprolol in contrast increased both parameters. Heart rate and cardiac output were similarly decreased in both treatment regimens.…”
Section: Epidural Anaesthesia/analgesiamentioning
confidence: 92%
“…Es gibt nur spärliche klinische und experimentelle Daten über Wirksamkeit und eventuell unerwünschte Effekte von kombinierten antiadrenergen Therapiekonzepten. Ein tierexperimenteller Vergleich zwischen thorakaler Epiduralanästhesie und β-AA bezüg-lich der Auswirkung auf hämodynamische Parameter bei wachen Ratten mit akutem Myokardinfarkt ergab folgende interessanten Resultate [9]: Während eine thorakale Epiduralanästhesien den linksventrikulären enddiastolischen Druck erniedrigte und der systemische Widerstand unverändert blieb, erhöhte Metoprolol dagegen beide Parameter. Herzfrequenz und Herzminutenvolumen ("cardiac output") wurden bei beiden Behandlungsgruppen gleichermaßen vermindert.…”
Section: Macht Es Sinn "Sympathikomodulierende" Therapien Zu Kombiniunclassified